(untitled) (Boletín Micológico, 2004)
A case report of an intrahospitalary Trichoderma longibrachiatum peritonitis in a female 13-year-old pediatric patient who had been previously diagnosed a terminal chronic renal insufficiency while being under peritoneal dialysis is presented. Nowasays literature recognizes certain members of the genus Trichoderma to be oportunistic pathogens of increasing occurrence in immunocompromised patients. The above girl recived a satisfactory Amphotericin B treatment yet she died due to an hypertensive emergency appearing secondarily to her basic pathology.